Usage of Simulation Games in Higher Educational Institutions teaching Economics and Business - Mirjana Pejić Bach; Maja Meško; Jovana Zoroja; Uroš Godnov; Tamara Ćurlin (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
Higher education institutions are embracing technology development and innovative teaching methods in order to prepare their students to be future professionals. New teaching frameworks extend existing learning approaches and set students as main characters of the learning process, which shifts the focal point from educators to students developing their abilities and knowledge. Psychology experts distinguished the role of games and play as an important factor in intellectual development a long time ago. Simulation games in education are widely acknowledged as highly effective methods, which produce numerous positive effects such as higher performance, engagement, and learning motivation. In this paper, we aimed to investigate the usage of simulation games in higher education institutions. The survey research has been conducted on a sample of 180 lectures at several faculties of economics in numerous European countries. The main goal of the paper is to investigate what is the level of usage of simulation games at faculties of economics, with the specific goals of comparing simulation games to the other types of teaching and discuss their advantages as well as barriers towards their usage.
Keywords: A2; O3; 330; simulation games; higher education institutions; technologies